Implementation of the Open Selection Policy for Primary High-Level Leadership Positions during the Acting Regent Period in Indonesia (Case Study in North Hulu Sungai Regency in 2023) - Rifie, Muhammad Zainal; Jamaluddin, Jamaluddin (Technium Social Sciences Journal, 2024)
This research aims to analyze the implementation of the open selection policy for high-level Primary (Pratama) leadership positions during the term of the Regent of Hulu Sungai Utara in 2023. This type of research is descriptive qualitative. Data collection was carried out using observation, interviews, and documentation. The data analysis technique is carried out through four stages, namely data collection, data condensation, data presentation, and conclusion. The results of the research show that the implementation of the open selection for Pratama high leadership positions during the term of Acting Regent of Hulu Sungai Utara has been carried out well in terms of the preparation stage, implementation stage, and monitoring and evaluation stage. Apart from that, looking at aspects of Edward III's implementation theory, namely: 1) Communication, the communication process from the source of information to the resulting impact, influences the efficiency and effectiveness of the implementation of open selection; 2) Resources, emphasizing that the quality and quantity of these resources greatly influences the smoothness and integrity of the implementation of the open selection; 3) Disposition, the process of appointing bureaucrats and the use of incentives as motivation factors; and 4) Bureaucratic Structure, Standard Operating Procedure which is not integrated between government agencies and fragmentation shows that separation in the implementation process can hamper the efficiency and effectiveness of the implementation of open selection and the inauguration of high-level pratama officials.